Dicotomias conceituais: análise sobre a concepção de promoção da saúde utilizada no Programa Saúde na Escola e na Estratégia Saúde da Família - Lucena, Carla mousinho Ferreira (2015)
Health Promotion is considered an important strategy for overcoming the development of purely curative and individual actions aimed at health, which are characteristic of the biomedical model. The same proposes the development of care, preventive and promotional health. However, this proposal reflects numerous obstacles, among them stands out the conceptual aspect, which was being shaped over the years from the development of understanding of the concept of health. Based on the scope of health promotion, the School Health Program was created in 2007, the same propose to the articulation of the Family Health Strategy with the school and it is proposed to integrate and link the two sectors with actions that aim to improve the quality of life of students in basic education schools. Thus, the present study was to identify the program inconsistencies from the design of health promotion that it incorporates in confront the understanding that the World Health Organization has about the same which is based on seven principles, which are: holism, intersectionality, empowerment, social participation, equity, multi-strategy actions and sustainability. This is a bibliographic and documentary research. Data collection occurred in the period from January to June 2014. Initially a literature review was conducted through a prior reading of titles and abstracts of articles, dissertations and theses contained in the scientific material to be defined. The collection was conducted with the Scielo databases ; Bireme ; Lilacs ; Medline and Cochrane Library , and the descriptors were used: health promotion; school health ; School Health Program ; Health strategy and school health . 35 articles and eight dissertations were obtained . This step was followed by desk research. As a result was obtained that: can not identify specifically that health promotion is adopted as nuclear center of the program; there is the definition of a concept of health promotion, before there is a mix of concepts that can be seen from the recommended actions; the structural difficulties faced by the FHS compromise its operation; predominates the trend of personal guilt is individual as your reality, is the professional regarding the commitment to the success of the proposed actions; do not see the incorporation of the seven principles defined by the WHO; the preponderance given to the health sector to conduct the proposed actions indicates serious weakness; the actions that stand out are the healing and promotion actions are confused with prevention. Therefore, identifies the importance of commitment to the critical evaluation of the program and the involvement of many other sectors of the political sphere and the active participation of individuals to the development of actions that are consistent with the broader concept of health and can focus the social determinants.